ANALISIS STILISTIKA PADA PUISI “KEPADA PEMINTA-MINTA” KARYA CHAIRIL ANWAR - Ini Aspriani; Ai Purwati; Restu Bias Primandhika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to describe the use of language in the poem "Kepada Peminta-Minta" by Chairil Anwar. In the poem, Chairil Anwar uses many word choices with the intention of beautifying the poem in his own style, so that the reader is interested in finding out and understanding. The approach used in this analysis is the stylistic approach, which approach is suitable for use because it can affect creativity. Based on the results of the analysis, this poem emphasizes many aspects of word formation such as the use of language that encourages readers to truly understand the use of these languages so that the meaning contained in them can be known. In his poem that he created, Chairil Anwar was very expressionistic.